The Influence of Peers and Learning Motivation on Students' Learning Outcomes in The Subject Of Social Sciences In Grade VIII - Kevin Risdianto; Anton Luvi Siahaan; Benjamin Albert Simamora (CV Putra Publisher, 2025)
This study aims to gain insight into the influence of peer relationships and learning motivation on student learning outcomes in Social Studies at SMP Negeri 6 Pematangsiantar. This research is quantitative with a descriptive approach. The population was all 209 grade VIII students of SMP Negeri 6 Pematangsiantar. The sample size was 137 students. The sampling technique used was simple random sampling. The data collection technique used was a questionnaire. The results of this study state that: 1) There is a positive and significant influence between peers on learning outcomes, these results can be seen in the t test where the t count value of peers (1.952) < t table (1.656), and the significant value (0.04) > α (0.05) which means that the variable is significant. 2) There is a positive and significant influence between learning motivation on learning outcomes, these results can be seen in the t test where the t count value of learning motivation (2.530) > t table (1.656) and the significant value (0.03 < 0.05) which means that the variable is significant. 3) Peers and learning motivation together influence student learning outcomes, these results can be seen in the F test where the F count value (4.09) > F table value (3.06). The R-square coefficient of determination test was found to be 0.416, indicating that peer group variables and learning motivation influenced student learning outcomes in social studies for grade VIII students at SMP Negeri 6 Pematangsiantar by 41.6%. The remaining 58.4% was influenced by other variables not examined in this study